"HYDROCEPHALUS: CAUSES, PATHOPHYSIOLOGY, DIAGNOSIS, AND TREATMENT APPROACHES-A REVIEW" - Muskan Parween; Sageer Ahmad; Rajesh Kumari Patil; Hanumanthrao C Patil (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Hydrocephalus, commonly known as "water on the brain," is a neurological disorder characterized by the abnormal accumulation of cerebrospinal fluid (CSF), leading to brain enlargement. This condition can result from various factors, including age, genetic predisposition, infections, and other underlying causes. Hydrocephalus is classified into two main types: communicating hydrocephalus, where CSF flow is blocked after leaving the ventricles, and non-communicating hydrocephalus, where the obstruction occurs within the ventricular system. Diagnosis typically involves imaging techniques such as MRI, ultrasound, and CT scans. Treatment options include medications like diuretics to manage fluid buildup and surgical interventions such as shunt placement or endoscopic procedures to restore normal CSF flow.